2015
DOI: 10.1037/a0039543
|View full text |Cite
|
Sign up to set email alerts
|

Narcissism and United States’ culture: The view from home and around the world.

Abstract: The issue of Americans' levels of narcissism is subject to lively debate. The focus of the present research is on the perception of national character (PNC) of Americans as a group. In Study 1, American adults (N = 100) rated Americans as significantly more narcissistic than they perceived themselves and acquaintances. In Study 2, this finding was replicated with American college students (N = 322). PNC ratings of personality traits and externalizing behaviors revealed that Americans were perceived as disagree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 85 publications
0
20
0
1
Order By: Relevance
“…Cultural influences are considered to play a substantial role in the development and maintenance of a narcissistic self. Initial studies that compared narcissism in different world regions suggest that narcissism is more prevalent in Western cultures (United States and, to a lesser extent, Europe) than in Eastern cultures (Asia; Foster, Campbell, & Twenge, ; Miller et al, ). Some researchers further identified an increase in narcissism across time (“generation me”; e.g., Twenge, Konrath, Foster, Campbell, & Bushman, ), whereas others found little support for generational changes in narcissism (e.g., Grijalva et al, ; Roberts, Edmonds, & Grijalva, ; Trzesniewski & Donnellan, ).…”
Section: The Narcissistic Personalitymentioning
confidence: 99%
“…Cultural influences are considered to play a substantial role in the development and maintenance of a narcissistic self. Initial studies that compared narcissism in different world regions suggest that narcissism is more prevalent in Western cultures (United States and, to a lesser extent, Europe) than in Eastern cultures (Asia; Foster, Campbell, & Twenge, ; Miller et al, ). Some researchers further identified an increase in narcissism across time (“generation me”; e.g., Twenge, Konrath, Foster, Campbell, & Bushman, ), whereas others found little support for generational changes in narcissism (e.g., Grijalva et al, ; Roberts, Edmonds, & Grijalva, ; Trzesniewski & Donnellan, ).…”
Section: The Narcissistic Personalitymentioning
confidence: 99%
“…Research has consistently identified that both Americans and non-Americans alike view the typical American to be very high in trait narcissism and Extraversion, and low in Agreeableness. In fact, both American and non-American participants in several previous samples rate the average American as meeting diagnostic criteria for an NPD diagnosis under DSM-5 (Miller et al, 2015), despite the fact that this tends to be a relatively infrequent diagnosis. Despite the pervasiveness of this distorted perception of Americans' national character, the particular mechanisms by which this view is developed and maintained are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…We estimated a medium effect size of Cohen's d = 0.5, a conservative estimate based on the finding from Miller et al (2015) that high visibility exemplars (e.g., actors/actresses) were rated as significantly more narcissistic (d = 1.03) than low visibility exemplars (e.g., teachers). Analyses indicate that for an independent sample t-test with power of 0.9 to find a medium effect at a significance level of .05, 86 participants were needed in each condition, suggesting that this study (N = 300) was sufficiently powered for a medium effect.…”
Section: Methods Power Analysis and Preregistrationmentioning
confidence: 99%
See 2 more Smart Citations